2022
DOI: 10.1080/07853890.2022.2114606
|View full text |Cite
|
Sign up to set email alerts
|

The main decision-making competence for willingness-to-pay towards COVID-19 vaccination: a family-based study in Taizhou, China

Abstract: Purpose This research aimed to explore individuals’ willingness to pay (WTP) and studied the role of family decision makers in WTP for COVID-19 vaccines. Methods A self-administered online questionnaire evaluating the willingness of community residents to pay for booster vaccination of COVID-19 vaccine was conducted among families in a community in Taizhou, China. The logistic regression model was performed to identify the factors associated with WTP for the COVID-19 va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
(27 reference statements)
1
2
0
Order By: Relevance
“…This is the first study to have examined the influence of the decision-making competence on vaccine hesitancy among college teachers; we found that the proportion of vaccine hesitancy among primary decision-makers was significantly lower than that among non-decision-makers (34.8% vs. 60.3%). This result is in line with our previous findings that the family decision-makers were more willing to pay for COVID-19 vaccines in a community of Taizhou, China [ 28 ]. Decision-making regarding proactively taking the COVID-19 vaccine for family may be modulated by concerns about the safety and effectiveness of the vaccine [ 46 ]; considering this, health promotion of the risk-benefit relationship of vaccination for family decision-makers must be urgently undertaken.…”
Section: Discussionsupporting
confidence: 92%
“…This is the first study to have examined the influence of the decision-making competence on vaccine hesitancy among college teachers; we found that the proportion of vaccine hesitancy among primary decision-makers was significantly lower than that among non-decision-makers (34.8% vs. 60.3%). This result is in line with our previous findings that the family decision-makers were more willing to pay for COVID-19 vaccines in a community of Taizhou, China [ 28 ]. Decision-making regarding proactively taking the COVID-19 vaccine for family may be modulated by concerns about the safety and effectiveness of the vaccine [ 46 ]; considering this, health promotion of the risk-benefit relationship of vaccination for family decision-makers must be urgently undertaken.…”
Section: Discussionsupporting
confidence: 92%
“…The participants completed a self-administered survey by scanning a QR code. We chose a community in Taizhou, China, and collected questionnaires from every household in the community ( Luo et al, 2022 ). A logical check was performed, and outliers were eliminated before data analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The family decision maker makes decisions within the family that affect the choices of the entire family ( Luo et al, 2022 ). Children rely on their parents and other family members to manage complex healthcare decisions owing to their lack of judgment and autonomy ( Gutman et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%